Characterization of bicycle mobility on the campus Rodrigo Facio, University of Costa Rica - Hernández Vega, Henry (2017)
This paper aims at characterizing bicyclists commuting to the University of Costa Rica, by analyzing the results of the Transportation Survey conducted in 2013 by the Transport Infrastructure Program (PITRA) of the National Laboratory of Structural Models and Materials of the University of Costa Rica. The collected data determined that 42% of respondents commute between two and five kilometers. In addition, 62% take 30 minutes or less to get to the university every day. There is a difference on bicycle use per sex given that 81% of cyclists are men and 19% are women. The lack of exclusive spaces for bicycles is one of the main problems experienced by cyclists. Vehicles at high speed, heavy vehicles on the road, and the lack of road lighting at night are some of the factors that influence the perception of cyclist safety. Finally, exclusive cycling infrastructure, bicycle parking spaces and driving education are considered the main incentives to ride a bicycle.